1993
DOI: 10.1111/j.1365-2222.1993.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Atopy in childhood. I. Gender and allergen related risks for development of hay fever and asthma

Abstract: Reasons for the gender differences in prevalence rates for asthma remain unclear. We have examined the relationships between allergen skin-test reactions and diagnoses of hay fever and asthma in New Zealand boys and girls examined at the age of 13 years. Information on current and past wheezing, diagnosed asthma, and hay fever was obtained for 662 subjects (341 boys) of a birth cohort followed longitudinally to the age of 13 years, using a physician-administered questionnaire. Atopic status was determined by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
113
3
5

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(148 citation statements)
references
References 30 publications
27
113
3
5
Order By: Relevance
“…Male and female children in the present study did not differ in weight, height or age. Female children were not expected to have a higher prevalence of atopy or mild asthma and symptom scores did not differ between males and females (p=0.48) [23,24]. As atopy was not measured specifically, a difference in atopic status between males and females may still be possible in this relatively small sample.…”
Section: Discussionmentioning
confidence: 99%
“…Male and female children in the present study did not differ in weight, height or age. Female children were not expected to have a higher prevalence of atopy or mild asthma and symptom scores did not differ between males and females (p=0.48) [23,24]. As atopy was not measured specifically, a difference in atopic status between males and females may still be possible in this relatively small sample.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the combination of asthma and allergic rhinitis was seen in over 80% of the patients in the two age brackets, which is in accordance with studies indicating that nasal symptoms occur in 30-80% of all patients with asthma and in up to 99% of those who are atopic. (20) Studies have shown that rhinitis and asthma are interrelated, and that the appropriate treatment of allergic rhinitis improves asthma control, decreasing symptoms and reducing the risk of emergency room visits and hospitalizations. (21)(22)(23)(24)(25) Indeed, 35 children in the ProAR-FS with mild asthma (23.6% of the sample of children and adolescents) and persistent rhinitis, using exclusively nasal corticosteroid, were not hospitalized, and there was a decrease of 84.2% in the frequency of emergency room visits during monitoring in the ProAR-FS.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 We found a similar effect in the univariate analysis; some of this effect was explained by atopy to dust mites and cat in the multivariate analysis. Sears et al 24 also found that gender differences for asthma reduced after adjustment for skin-test responsiveness to house dust mite and/or cat. Reasons for the residual excess prevalence among boys are unknown.…”
Section: Demographic Factorsmentioning
confidence: 96%